Environmental Management on Natural Lake Using Sediment and Hydrology Hydraulic Models - Mohd Khairul Amri, Kamarudin; Che Mansor, Jusoh; Hafizan, Juahir; Azman, Azid (2016)
The hydrology hydraulic model is established to assess environmental information on hydrology which can be used to investigate causes of various environmental problems at the river and natural lake catchment. This study reports on sediment concentrations at a river using a gravimetric method to investigate the hydrology system at a lake catchment. The measurement was carried out at the upstream, midstream, and downstream stations on the river in normal, rainy and post-rainy seasons. The stations are located along the Chini River, which are connected to a catchment lake (located at latitude 3°26’36.41”E-3°27’03.26”E and longitude 102°54’31.94”N-102°53’35.49”N). From the measurements, it is estimated that on average 787.621 tonne/km2 of sediment is transferred into the natural lake via Chini River annually. The correlation of statistical analysis between the sediment load and discharge study was very significant (R2 = 0.980). There is a linear relation between the area of the catchment and sediment load of the connecting river as supported by other studies in Malaysia. The outcome of the study suggests that the high sedimentation is due to land use activity, existence of the dam at the downstream of Chini River that traps the sediment, reverse flow from the Pahang River into Chini River and riverbank erosion factors. From this study, the sediment control steps are suggested such as creating conservation partially at the lake catchment, modifying the dam system, riverbank erosion control, and application of “Monkey Cheek” system. These sediment control steps may help to clean up the high suspended sediment at the whole lake system area, hence solving and mitigating the environmental problems in the natural lake catchment.